microRNA-1296 Inhibits Glioma Cell Growth by Targeting ABL2 - Gaolian Zhang BA (Technology in Cancer Research & Treatment, 2021)
Aberrant expression of microRNAs (miRNAs) has been reported to play a role in tumorigenesis. Dysfunction of miR-1296 was found in a variety of cancers, however, the function of miR-1296 in the progression of glioma remains largely understood. Here, our results showed that miR-1296 was significantly down-regulated in glioma tissues and cell lines. Decreased expression of miR-1296 was associated with the tumor size, WHO grade and karnofsky performance scale (KPS) of glioma patients. Low expression of miR-1296 was significantly correlated with the shorter 5-year overall survival of glioma patients. Overexpression of miR-1296 inhibited the proliferation, colony formation, migration and induced apoptosis of glioma cells. MiR-1296 was found to bind the 3’-untranslated region (UTR) of ABL proto-oncogene 2 (ABL2) and subsequently repressed both the mRNA and protein expression of ABL2. ABL2 was overexpressed in glioma tissues and inversely correlated with that of miR-1296. Ectopic expressed ABL2 could reverse the inhibitory effects of miR-1296 on glioma cell proliferation. Our results illustrated the novel tumor-suppressive function of miR-1296 in glioma via repressing ABL2, suggesting a potential application of miR-1296 in the treatment of glioma.